Designing and explaining the profit predictability assessment Model in Companies active in the financial industry - zahra hammami; Hasan Ghodrati; Meysam Arabzadeh; Hossein Panahian; Mohammad Alipour (ارزش آفرینی در مدیریت کسب و کار, 2023)
The profit predictability of the company's future performance is based on accounting information. It uses the information obtained from these forecasts to determine the company's value from the point of view of users of financial statements. Therefore, the current research was conducted with the aim of designing and explaining the profit predictability assessment Model in Companies active in the financial industry. This qualitative research was compiled using thematic analysis; In this research, by using semi-structured interviews with 18 experts in the field of accounting, as well as reviewing related researches, the findings were combined and the present model was designed. Based on this, by analyzing the content of the interviews and researches using the MaxQda2020 software, the relevant dimensions were extracted and the importance and priority of each was determined using Shannon's entropy technique. Based on the research approach, 28 components were extracted and the company's information environment, deviation analysis, profit variability and financial leverage analysis obtained the highest coefficient of importance using Shannon's entropy technique. In this research, the profit predictability evaluation model was presented in the form of 28 components. Since a comprehensive model has not been provided to evaluate the predictability of profits, this research can be useful in the direction of emerging challenges, profitability and improving the ability of Companies active in the financial industry to create scenarios. Extended Abstract Introduction Profit is one of the most prominent and significant items on financial statements that attracts financial statements users' attention. Investors, lenders, managers, company employees, analysts, the government, and other users of financial statements use profit as a basis for investment decisions, loan granting, interest payment policies, evaluating companies, calculating taxes, and other decisions pertaining to the company (Rauličkis et al., 2019). Profit, from an informational standpoint, represents the result of economic activities. Numerous investors favor companies with a consistent, profitable trend. Moreover, investors believe companies with fluctuating profits are riskier than those with stable profits (Gedviliene et al., 2018). In other words, profit is one of the most accurate measures of economic activity. Shareholders, as the most significant group of users of financial statements, scrutinize profit-related information. Investment, decision-making, and forecasting are guided by profit. Among the qualitative characteristics of profit are its sustainability, predictability, relevance, timeliness, and conservatism (Cheema et al., 2017). Forecasting is a crucial aspect of economic decision-making. Investors, creditors, management, and others rely on predictions and expectations in making economic decisions. Since investors and financial analysts use profit as a primary criterion for evaluating companies, they measure future profitability when deciding whether or not to retain or sell their shares. They evaluate the status of a company based on profit projections (Tian et al., 2021). The current and future profitability level of companies is the most important criterion for investors when selecting investment companies, so investors make decisions regarding various investment strategies based primarily on profitability. From the perspective of users of financial statements, the ability to predict the company's future performance based on accounting data and to utilize the information derived from these forecasts is crucial for determining the company's value. Therefore, accounting profit and its related components are among the factors individuals consider when making decisions. Information about the predictability of future profits is essential and helps forecast future profits. Based on the above background, the present research aims to design and explain a model for assessing the predictability of profit in companies active in the financial industry between 2011 and 2019. Valuable information regarding the predictability of profits aids in predicting future profits. This information typically covers the existing literature and research that determines a company's value from the financial statement users' perspective. Therefore, accounting profit and its related components are among the factors individuals consider when making decisions. The information related to the profit predictability is important and helps the future profit predict. The current study presents a useful model for developing research literature and will close the existing research gap. In this regard, this study sought to answer the following research question: How do companies active in the financial industry evaluate the predictability of their future profits? Theoretical framework Profit prediction is the ability of current profit to predict future profit in the short and long term. Profit projections provide management with information about the future of the company. Profit volatility is one of the factors that should be considered in profit forecasting; predictability has an inverse relationship with profit volatility (Cai et al., 2017). This criterion is defined as profit's ability to predict its own future. Predictability is one of the relevant components of the Financial Accounting Standards Board's (FASB) theoretical framework. Therefore, profit is desirable from the standard-setter's perspective (Ali et al., 2017). As a quality and time series characteristic of profit, profit predictability is the capacity of current profit to predict future short- and long-term profit. Among the factors that influence the relationship between volatility and profit predictability are economic and accounting factors (Skvarciany & Simanavičiūtė, 2018). Profitability predictability is one of the quality characteristics that enhance the relevance of accounting information. Examining the relevant literature reveals that numerous researchers have included predictability as one of the characteristics of profit time series. Several analysts view predictability as a distinct indicator of profit quality. On the other hand, others place predictability under a separate heading referred to as qualitative characteristics of accounting information criteria. Methodology The current research is based on qualitative research in the inductive paradigm and is applicable in terms of purpose. This study's statistical population consisted of accounting experts, including professors of the disciplines above, and managers and business owners in the financial sector. Per the study's objectives, 18 individuals were sampled in a targeted manner using the snowball method. The sample size was determined using the principle of theoretical saturation so that no new factors were observed after interviewing the 16th and 17th individuals, and the process of interviewing the 18th individuals was completed. Face-to-face interviews with open-ended questions were conducted, and then, using the coding procedure, 28 factors affecting the assessment of profit predictability were identified. MAXQDA 2020 software was utilized for coding. To ensure the coding and concept extraction accuracy, the codes obtained from the interviews were provided to the interviewees once more to obtain their approval of the extracted codes. The objective was to discover the interviewee's main point. In addition to expert interviews, domestic and international publication databases were examined in this study, focusing on articles relating to the ability to predict profit based on the reflection of previous studies in articles published between 2010 and 2022. Discussion and Results This research identified and categorized five concepts and 28 components of profit predictability evaluation based on interviews analyzed using the method of theme analysis and a review of previous research. This stage's findings indicate that such a systematic and exhaustive study has not yet been conducted. Each study has focused on a particular aspect and has not been presented comprehensively and systematically. Components of profit predictability evaluation include profit smoothing, company information environment, deviation analysis, disclosure requirement, biases, company market value, profit process complexity, environmental consciousness, volatility, time series techniques, unsystematic risk, expectations analysis, profit variability, operating cycle length, managers' opportunism, news accumulation, point forecasting, financial statement items, information accumulation, financial leverage analysis, forecasting horizon, past forecasting behaviors, company size, identification of stable components, and information symmetry are all factors that can influence the accuracy of projections, where conservatism is the estimation of items and the quality of matching income and expenses. Conclusion Accounting and the preparation of financial statements serve to provide decision-makers with useful information. The capacity to predict financial statement items is one manifestation of this usefulness. Investors, managers, financial analysts, researchers, and lenders have long been interested in forecasting accounting profit and its impact on economic decisions. This interest is a result of the use of profit in stock evaluation models, which contributes to the efficient functioning of the capital market, solvency assessment, risk assessment, economic unit performance evaluation, and the use of profit forecasts in the discussion of profit smoothing for management decisions, as well as the use in economic, financial, and accounting research. This study was conducted to design and explain the model for evaluating the ability to predict profit. According to the results of Shannon's entropy applied to the company's information environment, deviation analysis, profit variability, and financial leverage analysis are the most crucial factors. The subject of the research was the absence of a comprehensive model in the studied society and the neglect of the study gap's effective components, which prompted the researchers to develop a model. In this study, through expert interviews and a review of prior research, new dimensions of profit predictability were introduced with a more detailed and accurate look. Finally, a stage model was presented to design the model of this phenomenon according to the native conditions of the country, thereby reducing the amount of dispersion among previous research findings and emphasizing coherence and integration. This study aimed to fill the gap left by previous research to provide a comprehensive and step-by-step model for evaluating the predictability of profit. In their research, Alarussi and Alhaderi (2018) mentioned company size and financial leverage. They concluded that there is a positive relationship between company size and profitability and a negative relationship between leverage and profitability, which support the findings of this study. Moreover, the research findings of Yohn (2018) are consistent with the use of financial statement information. Fazlzadeh et al. (2019) referenced the investigation of the effect of news on profitability and profit forecasting, which is consistent with the present study's findings. In this regard, conducting a comprehensive analysis of financial leverage and the possibility of enhancing profit predictability through its application is suggested. In leveraged companies, profitability can be achieved by analyzing and matching the return on equity to the amount of debt. If the shareholders' rights exceed the company's debt, the company's use of debt may have a negative impact on its profitability. A weak and ineffective information environment decreases participation and diminishes profits. It also affects expenses and income compared to when sufficient and complete information is available. It is recommended that the company's information environment be improved and information circulation is accelerated. The more the deviations from the profit forecast are reduced, and the management can correctly identify and direct these deviations, the better the company's image will be, and the more accurately the profit will be reflected.